The effect of processing conditions on the mechanical properties and morphology of self‐reinforced wood‐polymer composite. Issue 10 (4th July 2013) - Cai, Jianchen; Jia, Mingyin; Xue, Ping; Ding, Yun; Zhou, Xiang
<x xml:space="preserve">Abstract</x> Highly oriented self‐reinforced round rods were produced from wood‐polymer composite (WPC) by solid‐state extrusion through a conical die. The effects of processing parameters such as draw ratio and die temperature on density, physical properties, and molecular morphology of the rods were systematically investigated. The WPC rods show an increase in density and significant improvements in the tensile properties at higher draw ratio. The tensile strength and modulus reach to 81.6 and 2200 MPa, respectively, at draw ratio of 8. In addition, scanning electron microscopy and wide‐angle X‐ray diffraction were used to observe the morphology of self‐reinforced rods and it was found uniquely fibrous and highly oriented throughout the profiles. POLYM. COMPOS., 34:1567–1574, 2013. © 2013 Society of Plastics Engineers